Role of α-melanocyte stimulating hormone and melanocortin 4 receptor in brain inflammation - Lasaga, Mercedes Isabel (2008)
Inflammatory processes contribute widely to the development of neurodegenerative  diseases. The expression of many inflammatory mediators was found to be increased in central nervous system (CNS) disorders suggesting that these molecules are major contributors to neuronal damages. Melanocortins are neuropeptides that have been implicated in a wide range of physiological processes. The melanocortin alpha-melanocyte stimulating hormone (a-MSH) has pleiotropic functions and exerts potent anti-inflammatory actions by antagonizing the effects of pro-inflammatory cytokines and by decreasing important inflammatory mediators. Five subtypes of melanocortin receptors (MC1R-MC3R) have been identified. Of these, the MC4 receptor is expressed predominantly throughout the CNS. Evidence of effectiveness of selective MC4R agonists in modulating inflammatory processes and their low toxicity suggest that these molecules may be useful in the treatment of CNS disorders with an inflammatory component. This review describes the involvement of the MC4R in central anti-inflammatory effects of melanocortins and discusses the potencial value of MC4R agonists for the treatment of inflammatory-related disorders.